Communications numériques en santé - Nicolas Peirot (Communiquer)
This reading note is about the book Communications numériques en santé (2021), co-edited by Benoit Cordelier and Olivier Galibert. It aims at questioning digital communication in health through ICT social integration mechanisms. It gathers eight contributions that focus on various socio-technical information and communication devices through three themes: organizational and professional limits of health communication, the relationships between digital communication in health and the ethics of care and knowledge mediations in health.